Navigating Your 20s and Beyond: A Practical Guide for Growth, Faith, and Purpose - Kibara, Benjamin (Nairobi, Kenya ; BTI Publications, 2025)
Your 20s are a defining decade full of choices, opportunities, mistakes, and milestones. They can feel overwhelming, but they are also rich in possibility.